Highly efficient and recyclable Z-scheme heterojunction of Ag3PO4/g-C3N4 floating foam for photocatalytic inactivation of harmful algae under visible light. (March 2023) - Ding, Ning; Fei, Qian; Xiao, Dongdong; Zhang, Hui; Yin, Hongfei; Yuan, Chunyu; Lv, Huijun; Gao, Peike; Zhang, Yongzheng; Wang, Renjun
Abstract: Harmful algal blooms (HABs) have frequently occurred worldwide, causing marine ecosystems and human health risks. As an advanced and green oxidation technology, photocatalysis has potential to remove red tide algae using solar energy. Herein, in this work, Z-scheme photocatalysts of Ag3 PO4 /g-C3 N4 (APCN) floating foam with different mass ratios were fabricated for the algae inactivation. Under visible light irradiation, the 0.10APCN (0.10 mM AgNO3 ) composite photocatalyst could cause 91.8% of the loss in Karenia mikimotoi ( K. mikimotoi ) cell viability following 24 h and the removal rate of algae could reach to 86% after five successive cycles. The underlying mechanism of photocatalytic inactivation of harmful algae is proposed in this system. The photosynthetic efficiency of harmful algae is inhibited with the decrease of photosynthetic pigments, which are inactivated by the high levels of reactive oxygen species (ROS) (superoxide radical O2 − and hydroxyl radical OH) produced in Z-scheme photocatalytic system of the Ag3 PO4 /g-C3 N4 heterojunction under visible light. Meanwhile, the activities of antioxidant enzymes (i.e. POD, APX and SOD) are up-regulating with the overproduction of ROS going into the algae, causing the cytotoxicity and apoptosis of algae. This work not only reveals the mechanisms of photocatalytic inactivation of harmful algae, but also guides the design the construction of high active composite photocatalysts, and thus provides theoretical and practical significance for highly efficient and recyclable prospect of controlling of harmful algae. Graphical abstract: Image 1 Highlights: A floating Z-scheme heterojunction of Ag3 PO4 /g-C3 N4 was successfully constructed. The APCN photocatalyst exhibits an algae inactivation rate of 92% within 24 h. The floating photocatalyst can be easily collected for further use than traditional powder photocatalysts. The APCN photocatalyst exhibits that the removal rate of algae could reach to 86% after five consecutive recycles.